Academic Perceptions of Immigrant and Minority Postsecondary Students - DeBellefeuille, Bette; Abrami, Philip C. (Canadian Journal of Higher Education, 2018)
This investigation compared postsecondary students whose mother tongue was English and who were natives of Canada (TV = 117) with minority students (N = 91) in terms of: a) the perceived importance of a university education and the perceived likelihood of academic success; b) the estimated likelihood of success at both competitive and noncompetitive tasks; c) the causal attributions for task outcomes and affective reactions to those outcomes and d) one projective and fourobjective fear of success (FOS) measures. English Canadian students and minority students held equivalent views on the importance of a university education and a successful career. FOS scores did not differ between the groups regardless of the measure used, either for males or females. Although there were few differences between the groups in their reaction to competitive, achievement-oriented tasks, there were more differences between the groups in their reactions to noncompetitive tasks. Here, minority students expressed some negative affective reactions. The minority students believed that external factors, particularly luck, had a greater influence on task outcome than did English Canadians.